An Agile Development Method of Employee Co-op Shop Web-Based Sales Information System - Indriani, Anisa; Pramudito, Dendy K; Suherman (Jurnal Informasi dan Teknologi, 2024)
Constructing a sales information system is a critical step to improve the sales process of productivity and efficiency. Kopkar 24 MMF as an employee co-op shop which is involved in the procurement and distribution of fast-moving consumer goods. Nowadays, it still conducts manual transactions through order cards and these lead to numerous impediments on commercial development to gain more revenues. The goal of this study is to construct a web-based sales information system utilizing the Laravel framework trough an agile development method. This research specifically to streamline and expedite the transaction process including the storages of goods. An agile development method is used to ensure the system development occurs in iterative stages and can swiftly adapt business evolvement. This web-based sales information system contains five primary functionalities which are product management, employee management, transaction management, billing reports, and other elements that facilitate the sales process at Kopkar 24.